Self-reported low self-esteem due to poor maternal care improves with the existential approach in bipolar disorder: a case report - Hirakawa, Hirofumi; Terao, Takeshi; Kawano, Nobuko (Frontiers in Psychiatry, 2023)
Parental nurturing attitudes influence children and are linked to the establishment of self-esteem. Females who have experienced poor maternal care during their childhood may have low self-esteem, and this factor may significantly augment the likelihood of depression. Particularly, childhood maltreatment among individuals with bipolar disorder is associated with unfavorable clinical features, such as a heightened risk of severe manic, depressive, or psychotic symptoms, as well as suicide attempts. Here, we report a case of a woman with bipolar disorder who had self-reported low self-esteem due to poor maternal care, which subsequently improved via an existential approach. This existential approach confers meaning to the lives of every individual, even in the face of adversity. Our findings suggest that the existential approach may enable the discovery of more positive life values during times of hardship and could improve self-reported low self-esteem due to poor maternal and change the way of life in patients with bipolar disorder.